The epidemiology of asthma and its comorbidities in Poland – Health problems of patients with severe asthma as evidenced in the Province of Lodz. (March 2016) - Panek, Michał; Mokros, Łukasz; Pietras, Tadeusz; Kuna, Piotr
Abstract: Introduction: Population studies supply interesting data regarding the epidemiology, comorbidity and risk factors of asthma, which have direct clinical implications for patients. Objectives: The aim of the work was to evaluate the degree of severity of asthma in the studied group, the levels of anti-asthma treatment, the prevalence of asthma comorbidities and their influence on the clinical course of the illness. Patients and methods: The study encompassed 451 participants: 52.11% were asthma patients (study group) and 47.89% were healthy subjects (controls). Respiratory function tests, ACT™ test and skin prick tests were performed. Results: Asthma severity was mild in 14.89%, moderate in 49.36% and severe in 35.74%. Oral GCS were used by 29%, inhalers 44%, LABA 68%, SABA 67%, LAMA 6%, SAMA 14% and MX 16%. Rhinitis and allergy were significantly more common in patients. GERD and neurological diseases were risk factors for asthma, and GERD significantly intensified the risk of severe asthma. GERD, atherosclerosis, hypertension, ischaemic heart disease and other cardiac diseases, lipid disorders, COPD, and the presence of any neoplastic disease significantly worsened the degree of asthma control. Discussion: Severe asthma was a significant clinical issue in over 35% of cases. The most commonly-used group of drugs were LABAs, while inhaled GCS and LAMA were uncommon, especially among severe cases. A significant problem was the high percentage of systemic GCS used by severe cases. The most important risk factor for asthma, including its severe form, is GERD. Numerous comorbid conditions significantly worsen the degree of asthma control.